2018
DOI: 10.7717/peerj.4514
|View full text |Cite
|
Sign up to set email alerts
|

Assessing soil bacterial community and dynamics by integrated high-throughput absolute abundance quantification

Abstract: Microbial ecological studies have been remarkably promoted by the high-throughput sequencing approach with explosive information of taxonomy and relative abundance. However, relative abundance does not reflect the quantity of the microbial community and the inter-sample differences among taxa. In this study, we refined and applied an integrated high-throughput absolute abundance quantification (iHAAQ) method to better characterize soil quantitative bacterial community through combining the relative abundance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 47 publications
3
44
0
Order By: Relevance
“…This method will be useful in other areas that benefit from quantitative analysis, such as monitoring microbial communities during manufacturing of complex probiotic mixtures 56 and monitoring changes of host-associated microbial communities over time (e.g., in health, aging and development, disease progression, and during probiotic or other treatments). Applying absolute quantification [19][20][21][23][24][25][26][27][28]32,33 of microbial taxa to biogeographically relevant GI locations will provide researchers with new insights in how microbial communities affect host phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method will be useful in other areas that benefit from quantitative analysis, such as monitoring microbial communities during manufacturing of complex probiotic mixtures 56 and monitoring changes of host-associated microbial communities over time (e.g., in health, aging and development, disease progression, and during probiotic or other treatments). Applying absolute quantification [19][20][21][23][24][25][26][27][28]32,33 of microbial taxa to biogeographically relevant GI locations will provide researchers with new insights in how microbial communities affect host phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…These methods require a purified DNA sequence of known concentration from an organism not present in the sample and an estimate of the initial sample concentration to determine the amount of exogenous DNA to spike-in. Another group of anchoring methods, such as those that use flow cytometry 24 , total DNA 25 , or quantitative PCR (qPCR) [26][27][28] , measure the total concentration of cells, DNA, or amplicons to transform the relative abundances to absolute numbers. These methods have already demonstrated the value of quantitative microbiome analysis, yet microbiome researchers have not yet uniformly adopted these methods.…”
mentioning
confidence: 99%
“…All gene copy numbers were calculated from the standard curves of 16S rRNA and the ITS genes by using the ΔCt (cycle threshold) method. All qPCRs were conducted in triplicate (Fierer et al, ; Guinane et al, ; Lou, Li, Wang, Wu, & Xu, ; Reddy et al, ). Amplicons were extracted from 2% agarose gels and purified using the AxyPrep DNA Gel Extraction Kit (Axygen Biosciences, Union City, CA) according to the manufacturer's instructions and quantified with QuantiFluor‐ST (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, all of results in our study are based on the taxonomic relative abundance, but the reported studies have demonstrated that the observed differences with relative abundances can cover those with the actual taxonomic abundances Tkacz, Hortala & Poole, 2018). The method of combining the quantification and relative abundance of the microbial communities should be used in the further studies (Lou et al, 2018;Guo et al, 2019).…”
Section: Discussionmentioning
confidence: 82%